1972
DOI: 10.1099/00221287-73-3-501
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Fusidic Acid Resistance to the Penicillinase Plasmid in Staphylococcus aureus

Abstract: S U M M A R YIn four out of five strains of Staphylococcus aureus examined, genes determining fusidic acid resistance were associated with a penicillinase plasmid. In one strain (FAR 5), although the linkage was unstable, resistance to fusidic acid was co-transduced with resistance to cadmium ions and penicillinase production. Further evidence for a single plasmid in this strain was obtained by studying the physical nature of the plasmid DNA. The molecular weight of the entire linkage group was about I 6 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…Lacey & Grinsted (1972) showed that CCC-DNA could be detected in the pigmented strain FAR^ when it contained a penicillinase plasmid, but CCC-DNA could not be detected in derivatives of FAR^ which had lost the penicillinase plasmid but still formed pigment. Ethidium bromide/ CsC1-gradient centrifugation was carried out on radioactive lysates of antibiotic-sensitive derivatives of the pigmented strains 609 and 6936 : in neither case could a radioactive satellite of CCC-DNA be detected.…”
Section: Ethidium Bromide/ Cs Cl-gradien T Centrifugationmentioning
confidence: 99%
“…Lacey & Grinsted (1972) showed that CCC-DNA could be detected in the pigmented strain FAR^ when it contained a penicillinase plasmid, but CCC-DNA could not be detected in derivatives of FAR^ which had lost the penicillinase plasmid but still formed pigment. Ethidium bromide/ CsC1-gradient centrifugation was carried out on radioactive lysates of antibiotic-sensitive derivatives of the pigmented strains 609 and 6936 : in neither case could a radioactive satellite of CCC-DNA be detected.…”
Section: Ethidium Bromide/ Cs Cl-gradien T Centrifugationmentioning
confidence: 99%
“…a PF plasmid). Strain ~~4 0 0 2 was derived from U B~O O I by growth of the latter at 43 "C, which resulted in loss of ~U B I O I (Lacey & Grinsted, 1972). Strains ~~4 0 0 3 to ~~4 0 0 6 were spontaneous one-step fusidic acid resistant mutants derived from ~4 0 0 2 by selection on media containing fusidic acid.…”
Section: Methodsmentioning
confidence: 99%
“…However, since spontaneous mutation to fusidic acid resistance in S. aureus occurs at high frequency in vitro (Miller, 1971 ;Lacey & Grinsted, 1972) and because resistant staphylococci have sometimes been isolated after therapy (Lowbury et al,I 962), fusidic acid is usually administered in combination with other antibiotics, particularly the penicillins (Garrod et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In one of these (strain 649) there was a correlation between the presence of plasmid DNA and resistance to streptomycin, and it was inferred that this plasmid carried the genes coding for streptomycin resistance. The molecular weight of this plasmid is about 38 million daltons, which is at least twice that of any other staphylococcal plasmid characterised (Novick and Bouanchaud ;Lacey and Grinsted, 1972). The size of the plasmid that determines streptomycin resistance may explain why transduction of this resistance could not be detected.…”
Section: Discussionmentioning
confidence: 99%
“…I . GRINSTED AND R. W. LACEY Isolation of covalently closed circular DNA (CCC-DNA) on ethidium bromide-CsCl gradients, and analysis on sucrose gradients, was as described previously (Lacey and Grinsted, 1972). …”
mentioning
confidence: 99%